ANALISA YURIDIS TERHADAP KEKERASAN SEKSUALITAS DALAM PERKAWINAN MENURUT UNDANG – UNDANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Sultan Ahtar Buana Yaksa; Agus Ariadi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the legal framework governing sexual violence within marriage based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Sexual violence in marriage is often perceived as a taboo issue in society because such acts are considered private matters between husband and wife, and therefore frequently remain hidden and unreported. This research analyzes the forms of legal protection available for victims of sexual violence within marriage by employing a normative juridical research method. This method utilizes statutory and conceptual approaches through an examination of positive legal provisions, legal principles, and legal theories related to sexual violence and the protection of human rights. The findings of this study show that the legal instruments regulating and protecting victims of sexual violence in marriage are substantively adequate. However, the effectiveness of these regulations and protections remains highly dependent on the role of society and the government, including consistent law enforcement, a victim-centered approach by law enforcement officers, and increased legal awareness within the community.